Flexural ductility of lightweight-aggregate concrete beams - Bernardo, Luís F. A.; Nepomuceno, Miguel C. S.; Pinto, Hugo A. S. (Journal of Civil Engineering and Management, 2016)
This paper describes an experimental study on the flexural ductility of lightweight-aggregate concrete beams including concretes with compressive strengths between 22.0 and 60.4 MPa and dry densities between 1651 and 1953 kg/m3. Nineteen simply supported beams were tested until failure. Two symmetrical concentrated loads were applied at approximately one third of the span. Ductility was studied by defining ductility indexes. The main variables are the concrete compressive strength and the longitudinal tensile reinforcement ratio. It is shown that the parameter with higher influence on ductility is the longitudinal tensile reinforcement ratio. The test results are also compared with the requirements from some codes of practice. It is shown that ACI Code requirements give more guaranties as far as ductility is concerned, when compared with European codes.